MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS NEED ASSESSMENT SMP QORYAH THAYYIBAH SALATIGA - Hadi Nasroh (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to reveal the depth of Islamic education learning management need assessment based junior Alternative Qoryah Thayyibah In Salatiga. In line with the formulation of research that has been established, the purpose of this study include: (1) Know and find lesson plans based Islamic education needs assessment in the Junior Alternative Qoryah Thayyibah Kalibening Salatiga. (2) Know and find the implementation of Islamic Education based learning need assessment in the Junior Alternative Qoryah Thayyibah Kalibening Salatiga. (3) Know and find learning evaluation based Islamic education needs assessment in the Junior Alternative Qoryah Thayyibah Kalibening Salatiga. This study used qualitative methods, research design Case Study spikes. These results indicate that: (1) Planning Tawasih (Islamic Education) on SMP Qoryah Thayyibah planning and managing their own students, students who determine or term planning centered on the learner. (2) Implementation of the learning tawasih (PAI) which determines the student, junior high school students Qoryah Thayyibah given the freedom to think and act on the vision and mission of the school that the student be free man, responsible, critical and skilled. (3) System evaluation companion (teacher) in learning tawasih (Islamic Education) is returned to the student or student-centered. Because learning tawasih (Islamic Education) is more concerned with the work of students from the figures the results of any examinations including UAN though. Planning, implementation, evaluation of learning tawasih Principal should organize existing resources and teacher or chaperone in facilitating the learning of students in both learning tawasih in particular (Islamic Education) or learning in other science subjects, should be the attitude and thinking positive and avoid angry very detrimental to many parties.